Literature Study: The Role of Pancasila Education in the Formation of National Identity in Students in the Era of Globalization - Wafa, Alfian Fawaidil; Hanafi, Hanafi; Fattah, Zulfikar Waliyuddin (IJBLE Scientific Publications Community Inc., 2025)
This study examines the role of Pancasila education in shaping students' national identity in the era of globalization. This research is motivated by the significant influence of globalization on various aspects of life, especially culture and national identity. Globalization brings cultural shifts triggered by foreign cultures entering through the flow of global information. Pancasila education is crucial for strengthening the understanding and practice of the noble values of the Indonesian nation. This study aims to analyze the role of Pancasila education in strengthening national identity, especially among students as the nation's next generation. This study uses a literature study method to collect and analyze relevant sources. The results show that Pancasila education plays a role in building students' character based on Pancasila values, such as mutual cooperation, social justice, and respect for humanity. Pancasila education is also expected to overcome the challenges of globalization that can threaten the preservation of local culture and national identity. In conclusion, Pancasila education in higher education strengthens Indonesia's national identity by instilling the values of multiculturalism, tolerance, and the spirit of unity in diversity, which are relevant in the era of globalization